A prospective observational study on lymph node mapping of sentinel lymph node biopsy using methylene blue in carcinoma breast - John, Joel; U., Sansho E. (International Surgery Journal, 2020)
Background: Modern screening methods has made it possible to diagnose breast cancer in as early stage as possible and axillary lymph node status is still the most important prognostic indicator in carcinoma breast. In this study we are trying to analyse the preference of lymph nodal staining in SLNB using methylene blue in early breast cancer, so that surgeons will be more aware of anatomical positions of the stained nodes, thus favouring more precise dissection, reducing the morbidity. Methods: This was a prospective observational study conducted in the Department of General Surgery, Government Medical College, Kottayam. All cases of clinically N0 carcinoma breast undergoing modified radical mastectomy were included. We injected 3 ml of methylene blue in the subareolar region in three places depending on the quadrant in which tumour was situated, before putting the skin incision for modified radical mastectomy and the pathologist segregated the stained lymph nodes after confirming the anatomical locations. Results: The study here was diagnostic test evaluation and the diagnostic test being evaluated was sentinel lymph node biopsy using methylene blue. Commonest group of lymph nodes, where sentinel lymph nodes were identified were anterior group (30 out of 34 sentinel lymph nodes). Conclusions: Though sentinel lymph node biopsy using methylene blue is not a fool proof method; knowing the mode of methylene blue flow i.e., anterior more than central and then posterior group of lymph nodes will definitely reduce the morbidity involved, and above all saving time of the surgery.